Caracteristica fizico-geografică a râului Cubolta [Articol] - Chişca, Dionisia (USARB, 2021)
The article is dedicated to deepening and studying the physical-geographical aspect of the Cubolta River (physical-geographical position in the territory, description of the relief, hydrological regime, water quality, flora, fauna and anthropogenic impact on fishery resources).
Keywords: river; water quality; geographical characteristics; relief; fishery resources